The impact of corporate governance on financial performance In Saudi Joint Stock Companies - Al-Alma‘ai, Ali Fayz (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aimed at determining the impact of corporate governance on financial performance. The study examined the effect of the size of the board of directors, the composition of the board of directors, and the number of meetings of the audit committee on firm financial performance (return on assets, return on equity). In order to achieve the objectives of the study, method was used that collects sufficient data on the subject of the study and access to clear knowledge of the study problem. The comprehensive inventory method for insurers was used to obtain the data required for the study through published financial reports, based on the company’s financial performance. The main results of the study: - There is an impact on the size of the board of directors on the financial performance of the insurance companies (return on assets and return on equity). - There is an impact of the existence of executive members on the board of directors on the financial performance of insurance companies (return on assets and return on equity). - There is an impact of non- executive directors on the financial performance of insurance companies (return on assets and return on equity). - There is an impact on the number of board meetings on the financial performance of insurance companies (return on assets and return on equity). - There is an impact of the number of members of the Audit Committee on the financial performance of the insurance companies (return on assets and return on equity). - There is an impact of the number of Audit Committee meetings on the financial performance of insurance companies (return on assets and return on equity). Key recommendations include: - It is recommend that insurance companies should increase compliance with the requirements of corporate governance in order to reach the best proportion of application of the rules of corporate governance to ensure the positive impact of the rules of governance on financial performance. - The need to support the relevant departments of governance within the financial institution, such as the Department of compliance and internal and legal review and others.